2016
DOI: 10.1016/j.bbadis.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of P-glycoprotein in mediating rivastigmine effect on amyloid-β brain load and related pathology in Alzheimer's disease mouse model

Abstract: Recently, we showed that rivastigmine decreased amyloid-β (Aβ) brain load in aged rats by enhancing its clearance across the blood-brain barrier (BBB) via upregulation of P-glycoprotein (P-gp) and low-density lipoprotein receptor-related protein 1 (LRP1). Here, we extend our previous work to clarify P-gp role in mediating rivastigmine effect on Aβ brain levels and neuroprotection in a mouse model of Alzheimer’s disease (AD) that expresses different levels of P-gp. APPSWE mice were bred with mdr1a/b knockout mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 56 publications
1
41
2
3
Order By: Relevance
“…Consistent with this premise, findings from our laboratory support targeting clearance pathways of Aβ efflux across the BBB to reduce Aβ brain burden . Wild‐type and AD mice models' treatment with Abcb1 and Lrp1 inducers, including rifampicin, acetylcholine esterase inhibitors, and oleocanthal, were able to enhance Aβ brain clearance across the BBB and reduce its brain deposition.…”
Section: Targeting Transporters In the Treatment Of Neurological Disesupporting
confidence: 75%
“…Consistent with this premise, findings from our laboratory support targeting clearance pathways of Aβ efflux across the BBB to reduce Aβ brain burden . Wild‐type and AD mice models' treatment with Abcb1 and Lrp1 inducers, including rifampicin, acetylcholine esterase inhibitors, and oleocanthal, were able to enhance Aβ brain clearance across the BBB and reduce its brain deposition.…”
Section: Targeting Transporters In the Treatment Of Neurological Disesupporting
confidence: 75%
“…However, the absorption and distribution of the methylthioninium moiety is complex, and plasma concentrations do not reflect brain concentration. 14 Avenues being explored include further blood analyses, the potential effect of cholinergic pathology on cognition and brain atrophy 27 in tau transgenic mouse models, the interaction between cholinesterase and amyloid pathology, 28 and whether induction of transporters by chronic administration of symptomatic treatments for Alzheimer’s disease 29,30 might lower the concentration of methylthioninium at the site of action.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that accumulation of Aβ plaques in the AD brain may result from decreased levels of P-gp (Bruckmann et al, 2017;Mohamed et al, 2016). Studies have shown that accumulation of Aβ plaques in the AD brain may result from decreased levels of P-gp (Bruckmann et al, 2017;Mohamed et al, 2016).…”
Section: P-gp Induction Activity Of Embelin In Ls-180 Cellsmentioning
confidence: 99%